Audit Operasional untuk Mengukur Efektivitas dan Efisiensi Fungsi Penjualan di Saat Wabah Virus Corona - Syalsa Pramudi Efendi Putri; Yanti Rufaedah (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The purpose of this study was to deterrnine operational audit, analyze findings and provide recornrnendations, and rneasure the effectiveness and efficiency of the sales function at PT Falmaco arnidst rhe corona virus disease. This type of research is a descriptive study with a qualitative approach. This study uses data collection techniques by rneans of interviews, observation, and docurnentation. The results of the operational audit at PT Falmaco were quite effective and efficient because there is an increase in sales every rnonth accornpanied by an increase in sales cost efficiency. However, the increase in sales arnid the corona virus disease cannot be fully handled by the cornpany due to lirnited hurnan resources, distance, and tirne. As a results, cornpanies need to face and overcorne problerns related to the potential for lost revenue.